Close range digital photogrammetry and software application development for planar patterns computation (2009)
This paper shows there processes for the particular case of objects with complex surfaces: the 3D modelling of the object and its development to 2D model. The procedure to obtain accurate 3D CAD models of objects with complex surfaces through close range digital photogrammetry is described; several methodological considerations are presented that allow obtaining high accuracy results and minimize processing time. Furthermore a software application that calculates the corresponding planar profiles is developed. The application automatically outputs a CAD neutral file with the definition of the optimized planar patterns needed for the NC cutting machines. The computation of the planar patterns is based on the solution of an optimization problem that takes into consideration the geodesic curvature of the surface of the isoparametric curves.